HEPATITIS VIRUSES AND METHODS USED IN THEIR DIAGNOSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Hepatitis virus infections remain one of the leading causes of liver diseases and hepatocellular carcinoma worldwide. This article analyzes the pathogenesis and epidemiology of hepatitis A, B, C, D, and E viruses, with particular emphasis on diagnostic methods—serological tests, molecular techniques, rapid diagnostics, and screening strategies. The accuracy, limitations, and practical application of diagnostic methods are discussed. In addition, the use of modern technologies (such as nucleic acid amplification, quantification, and highly sensitive tests) in the diagnostic process is reviewed.